Distribution and spread of bark beetles (Coleoptera: Scolytidae) around the Gulf of Finland: a comparative study with notes on rare species of Estonia, Finland and North-Western Russia - Voolma, Kaljo; Mandelshtam, Mikhail; Shcherbakov, Alexander; Yakovlev, Eugene; Õunap, Heino; Süda, Ilmar; Popovichev, Boris; Sharapa, Tatiana; Galasjeva, Tamara; Khairetdinov, Roman; Lipatkin, Vladimir; Mozolevskaya, Ekaterina (Entomologica Fennica, 2004)
Along-term faunistic study of bark beetles (Coleoptera: Scolytidae), conducted in Estonia, as well as in Karelia, Leningrad (St. Petersburg) and Murmansk provinces of Russia, enables a comparison of the species composition of bark beetles in the regions bordering Finland. Altogether the distribution patterns of 83 species of scolytids are examined. The northern borders of the distribution range for Scolytus scolytus, S. multistriatus, S. laevis, Hylastes ater, H. opacus, Orthotomicus longicollis, Pityogenes trepanatus, Ips amitinus and Cryphalus abietis in Northern Europe are redefined. The list of bark beetles for Estonia and North- Western Russia (Karelia, Leningrad and Murmansk provinces) with their occurrence in some biogeographical provinces of Fennoscandia (Ik, Kl, Kon, Ks, Kk, Lim) is given. Recent records of bark beetles, endangered or rare in Finland, and their current distribution in the neighbouring regions are discussed.